2000
DOI: 10.1159/000016039
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a), Other Lipoproteins and Hemostatic Profiles in Patients with Ischemic Stroke: The Relation to Cardiogenic Embolism

Abstract: Lipoprotein and hemostatic profiles including coagulation inhibitors were determined in 136 patients with acute ischemic stroke. Based on clinical examination, cerebral computed tomography, Doppler ultrasonography of precerebral arteries and transthoracic echocardiography, the strokes were classified as cardioembolic (n = 38), non-cardioembolic (n = 92), and mixed cardioembolic/hypertensive (n = 6). Patients with cardioembolic stroke were older than patients with non-cardioembolic stroke. Lipoprotein(a) was hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Further studies are needed to confirm these results. Other studies have suggested that Lp(a) may be related to the increased stroke risk via coagulation markers of thrombosis rather than to risk factors associated with atherosclerosis [33]. We were unable to explore this pathway further due to limitations in our data collection.…”
Section: Discussionmentioning
confidence: 93%
“…Further studies are needed to confirm these results. Other studies have suggested that Lp(a) may be related to the increased stroke risk via coagulation markers of thrombosis rather than to risk factors associated with atherosclerosis [33]. We were unable to explore this pathway further due to limitations in our data collection.…”
Section: Discussionmentioning
confidence: 93%
“…D-dimer levels have been shown to be associated with cardioembolic strokes [4,6,7,8,9,10,12,14], yet their significance in acute stroke remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrate a role of Lp(a) as an important risk marker, partly independent of other risk markers, for the occurrence of an acute coronary syndrome and spontaneous, partly recurring, ischemic strokes and of venous thromboses and thromboembolism in children and adults [58,[90][91][92][93][94][95][96], while other investigations did not establish any relationship between the occurrence of thrombotic events or thromboembolism and the existence of an elevated Lp(a) plasma concentration [97][98][99]. Moreover, elevated Lp(a) plasma concentrations were measured in a number of studies performed in patients with early-stage or terminal kidney diseases and autoimmune diseases (antiphospholipid syndrome, systemic sclerosis, chronic thromboembolic pulmonary hypertension, rheumatoid arthritis and systemic lupus erythematosus), which fact supports the involvement of Lp(a) in the increased occurrence of thromboembolic events [100][101][102][103][104][105][106][107][108][109].…”
Section: Lp(a) In Hemostasismentioning
confidence: 99%